Sirtuin Control of Mitochondrial Dysfunction, Oxidative Stress, and Inflammation in Chagas Disease Models - Wan, Xianxiu; Garg, Nisha Jain (Frontiers in Cellular and Infection Microbiology, 2021)
Trypanosoma cruzi is an obligatory intracellular parasite with a digenetic life cycle. Trypanosoma cruzi replication in host induces immune-mediated cytotoxic proinflammatory reactions and cellular injuries, which are believed as a common source of reactive oxygen species (ROS) and nitrogen species (RNS) generation during acute parasitemic phase. Mitochondrial degeneration has also been proposed as a major source of ROS generation in chronic phase of the disease, which renders myocardium to be exposed to sustained oxidative stress that may contribute to the development of Chagas disease pathology. Sirtuin 1 (SIRT1) senses the redox changes and integrates mitochondrial metabolism and inflammation. In this review, we discuss the molecular mechanisms by which SIRT1 can potentially improve the mitochondrial function and control oxidative and inflammatory stress in Chagas disease.